2003
DOI: 10.1021/jp0350823
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Decarboxylation of Carbonyloxy Radicals:  Influence of Molecular Structure

Abstract: Experimental and theoretical investigations on the ultrafast photoinduced decomposition of three tert-butyl peroxides of general structure R-C(O)O-O-tert-butyl with R ) phenyloxy, benzyl, or naphthyloxy in solution are presented. Photoinduced O-O bond scission occurs within the time resolution (200 fs) of the pumpprobe experiment. The subsequent dissociation of photochemically excited carbonyloxy radicals, R-CO 2 , has been monitored on a picosecond time scale by transient absorption at wavelengths between 290… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 52 publications
7
77
4
Order By: Relevance
“…Figure 9 displays the D-E hysteresis loop of the Al/C 6 F 13 (VDF) 23 I/Al capacitor, and Table 8 summarizes the remanent polarization values (P r ), which were estimated from the D-E hysteresis loop of the samples. The results indicated that the P r values of all of the samples were similar (B100 mC m À2 ); however, P r values obtained in this study were lower than those observed in a previous study on CF 3 (VDF) 17 I (130 mC m À2 ). 6 The relatively low P r values observed in the current investigation may be due to the differences in the terminal chain length of R F (C n F 2n+1 ) groups, which are bulkier than CF 3 and do not contribute to polarization reversal.…”
Section: Piezoelectric Properties Of Vdf Telomers N Durand Et Alcontrasting
confidence: 66%
See 3 more Smart Citations
“…Figure 9 displays the D-E hysteresis loop of the Al/C 6 F 13 (VDF) 23 I/Al capacitor, and Table 8 summarizes the remanent polarization values (P r ), which were estimated from the D-E hysteresis loop of the samples. The results indicated that the P r values of all of the samples were similar (B100 mC m À2 ); however, P r values obtained in this study were lower than those observed in a previous study on CF 3 (VDF) 17 I (130 mC m À2 ). 6 The relatively low P r values observed in the current investigation may be due to the differences in the terminal chain length of R F (C n F 2n+1 ) groups, which are bulkier than CF 3 and do not contribute to polarization reversal.…”
Section: Piezoelectric Properties Of Vdf Telomers N Durand Et Alcontrasting
confidence: 66%
“…In the initiation step, radicals are generated by the thermal decomposition [17][18][19] of a conventional initiator, such as bis(4-tert-butylcyclohexyl) peroxydicarbonate (step a). For a temperature below 90 1C (in this article), the carbonyloxy intermediate radical does not undergo any decarboxylation.…”
Section: Mechanism Of Iodine Transfer Polymerizationmentioning
confidence: 99%
See 2 more Smart Citations
“…75 In the case of the benzoyloxy radical, the search was less time-consuming because of the highly symmetric structure of the saddle-point geometry. However, C 2V symmetry was not used in the calculations, but C 1 symmetry was adopted to account for the following situation: According to the first Hohenberg-Kohn theorem, 76 the Hamiltonian (i.e., the external potential) is uniquely defined by the electron density of the ground electronic state.…”
Section: Resultsmentioning
confidence: 99%